Disruption of Amino Acid Homeostasis by Novel ASCT2 Inhibitors Involves Multiple Targets - Bröer, Angelika; Fairweather, Stephen; Bröer, Stefan (Frontiers in Pharmacology, 2018)
The glutamine transporter ASCT2 (SLC1A5) is actively investigated as an oncological target, but the field lacks efficient ASCT2 inhibitors. A new group of ASCT2 inhibitors, 2-Amino-4-bis(aryloxybenzyl)aminobutanoic acids (AABA) were developed recently and shown to suppress tumor growth in preclinical in vivo models. To test its specificity, we deleted ASCT2 in two human cancer cell lines. Surprisingly, growth of parental and ASCT2-knockout cells was equally sensitive to AABA compounds. AABA compounds inhibited glutamine transport in cells lacking ASCT2, but not in parental cells. Deletion of ASCT2 and amino acid depletion induced expression of SNAT2 (SLC38A2), the activity of which was inhibited by AABA compounds. They also potently inhibited isoleucine uptake via LAT1 (SLC7A5), a transporter that is upregulated in cancer cells together with ASCT2. Inhibition of SNAT2 and LAT1 was confirmed by recombinant expression in Xenopus laevis oocytes. The reported reduction of tumor growth in pre-clinical models may be explained by a significant disruption of amino acid homeostasis.